Original paper Theoretical validity and reliability of Vespide Quality of Life Questionnaire in Polish adolescents with Hymenoptera venom allergy - Brzyski, Piotr; Cichocka-Jarosz, Ewa; Tobiasz-Adamczyk, Beata; Lange, Joanna; Świebocka, Ewa; Lis, Grzegorz; Jedynak-Wąsowicz, Urszula; Pietrzyk, Jacek J.; Kulus, Marek; Kaczmarski, Maciej; Małaczyńska, Teresa; Klajna-Kraluk, Barbara; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Measurement of health-related quality of life is mostly used with advanced measurement tools, such as scales. The use of a certain scale in different cultural settings or in age groups other than those it was designed for needs conducting the adaptation process and assessment of psychometric properties of the adapted scale. Aim: This paper presents the results of theoretical validity and reliability analysis of the Polish adaptation of the VQLQ scale for adolescents with Hymenoptera venom allergy. Material and methods : The study sample consisted of 78 adolescents aged 14-19 years, who were treated with venom immunotherapy in Polish allergological centers in 2008 year. Theoretical validity of the scale was analyzed with exploratory factor analysis using the principal components method. Reliability analysis was assessed in terms of internal consistency with Cronbach’s  coefficient and by testing Kline’s criterion. Results: The results showed satisfactory validity of the scale: factor analysis revealed a 3-factor structure of the scale – extracted factors were described as anxiety, caution and discomfort. All the scale items contributed to unique factors, except for one item concerning limitation in summer due to allergy, which was identified as a separate dimension of health-related quality of life of Polish adolescents with Hymenoptera venom allergy. All the extracted subscales were characterized by values of  coefficient equal or higher than 0.8, what is usually considered as a high-level reliability coefficient. Conclusions : The adapted scale is a valid and reliable tool measuring health-related quality of life in Polish adolescents treated with venom-specific immunotherapy.